Lingkungan dan Kearifan Lokal Masyarakat Muslim-Kristen Pesisir Banyutowo - Thiyas Tono Taufiq (Living Islam: Journal of Islamic Discourses, 2018)
The condition of Banyutowo coastal is currently worrying because of ecological problems such as household waste pollution, plastic waste buildup, sedimentation, and so forth. This study aims to clarify the local wisdom of Muslim-Christian communities on the Banyutowo coastal in growing responsibility in protecting the environment. The data collection is done by observation, interview or indepth interview with informants around the coastal and environment in Banyutowo. The obtained data is classified and analyzed using the analysis of etno-ecological approach, in which the Muslim-Christian community to see the reality and culture that exists. Banyutowo community problem faced at this time is the problem of garbage, where garbage piled almost along the shoreline, and there are some unscrupulous people who throw up at sea. Most cultures Muslim-Christian community tend to be homogeneous, because community in Banyutowo is Javanese. In addition, there is a tradition of the local community that is ritual "sedekah laut” (alms sea) that makes solidarity and strengthen community relationship without looking at background, religion, or other, the goal is to be blessed and given sal- vation in the sea.